Aspirin abrogates impairment of mammary gland differentiation induced by early in life second-hand smoke in mice. (17th May 2018) - Santucci-Pereira, Julia; Pogash, Thomas J; Patel, Aman; Hundal, Navroop; Barton, Maria; Camoirano, Anna; Micale, Rosanna T; La Maestra, Sebastiano; Balansky, Roumen; De Flora, Silvio; Russo, Jose
Abstract: Epidemiological studies show that there is limited evidence that tobacco smoking causes breast cancer in humans. In rodents, many tobacco smoke chemicals cause mammary gland tumors. This study evaluated the mammary gland differentiation in mice exposed to environmental cigarette smoke (ECS), using 3R4F Kentucky reference cigarettes, starting after birth and continuing daily for 10 weeks (total particulate exposure 95 mg/m 3 ; CO 610 ppm). We also analyzed the effects of oral administration of non-steroidal anti-inflammatory drugs (NSAIDs), aspirin (1600 mg/kg) or naproxen (320 mg/kg), on mammary gland differentiation, either in unexposed or ECS-exposed mice. The ECS exposure caused delay of mammary glands development. We speculate that this delay may result from aryl hydrocarbon receptor (AHR) signaling activation, which has an antiestrogenic effect and crosstalk to the estrogen metabolism pathway. Similarly, naproxen impaired gland differentiation in unexposed and ECS-exposed mice, while aspirin hindered its development only in unexposed mice. The lack of differentiation induced by the NSAIDs could be explained by their antiestrogenic effect through inhibition of aldo-keto reductases. In ECS-exposed animals, aspirin induced intense lobular formation, which could indicate that aspirin is counteracting the AHR signaling induced by ECS. Based on the differentiation induced by aspirin in ECS-exposed animals, we postulate that these mice would be less susceptible to mammary carcinogenesis. Our results suggest that exposure to smoke at an early age impairs the development of the mammary gland, thus resulting in a longer period of susceptibility and increased risk of breast cancer. However, addition of aspirin can abrogate this effect. Abstract : This study demonstrated for the first time that second-hand smoke at early age impairs mammary gland differentiation in mice, which could increase susceptibility to carcinogenesis. NSAIDs have similar effects; however, in animals exposed to cigarette smoke, aspirin abrogates its effect.